A Systematic Review of the use of Bupropion for Hypoactive Sexual Desire Disorder in Premenopausal Women - Alyssa J. Bolduan; David M. Haas (Journal of Women's Reproductive Health, 2015)
Objective: To assess the efficacy of bupropion therapy for hypoactive sexual desire disorder (HSDD) in women. Methods: A systematic review was performed utilizing the standard databases. Data were abstracted for study quality, characteristics, and outcomes. Due to the small number of studies and lack of consistently reported outcomes, a meta-analysis was not performed. Results: Two studies (289 women) met inclusion criteria. While one study had low risk of bias, the other had areas of high risk of bias. Both trials reported improvement in sexual function domains with treatment ranging from 12 weeks to 112 days. Conclusions: Despite two trials demonstrating benefit with bupropion treatment for premenopausal women with HSDD, the evidence is limited and not of adequate quality to recommend the therapy. More trials are needed in this area.
Keywords: bupropion